Group A streptococcal endophthalmitis complicating a sore throat in a 2-year-old child. (9th April 2015) - Fitzgerald, Felicity; Harris, Kathryn; Henderson, Robert; Edelsten, Clive
Abstract : A previously well 2-year-old presented to her general practitioner after 5 days of fever, lethargy, sore throat and a slightly red eye. A viral infection was diagnosed. Two days later, she re-presented with a swollen right eyelid and a moderately red eye. Oral amoxicillin and chloramphenicol eye drops were prescribed. The next day, marked periorbital swelling developed. She was admitted to hospital and parenteral ceftriaxone was started. Examination under anaesthetic showed injected globe diffuse corneal clouding and peripheral corneal opacities; ultrasound and CT suggested endophthalmitis. On transfer to a tertiary centre, intraocular vancomycin and subconjunctival cefuroxime were given. Aqueous fluid samples were positive for group A Streptococcus (GAS) by PCR, so parenteral clindamycin was added. GAS endophthalmitis was confirmed 1 day later from the positive intraocular fluid culture results. Visual evoked potentials revealed complete loss of vision. The eye was removed to limit potential spread. She made a good recovery postoperatively and was discharged on oral antibiotics.